2017
DOI: 10.3390/su9030469
|View full text |Cite
|
Sign up to set email alerts
|

International Project Risk Management for Nuclear Power Plant (NPP) Construction: Featuring Comparative Analysis with Fossil and Gas Power Plants

Abstract: Abstract:The concern of risk management has continuously increased in international construction projects. International projects have a high level of risk and complexity, which results in greater possibilities of cost overruns and schedule conflicts when compared with local projects. Therefore, the goal of risk management is to improve project performance by systematically identifying and assessing project risks, developing strategies to reduce or avoid risks and to maximize opportunities. However, there have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 17 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…The owner (or government entity) has sole responsibility for finding suitable land for the project, but many projects are delayed in reality. This prevents the contractors' access to the land, thereby incurring extra costs (Kucukali 2016) for socio-political reasons, for instance, unsettled land with the owner (Sudirman and Hardjomuljadi 2011), environmental issues, and lack of cooperation between government organizations (Kim et al 2017). The availability of materials and equipment in the local market is also a major factor responsible for increasing project cost as a result of a delayed procurement process (Pall et al 2016).…”
Section: Discussion Of Important Risksmentioning
confidence: 99%
See 1 more Smart Citation
“…The owner (or government entity) has sole responsibility for finding suitable land for the project, but many projects are delayed in reality. This prevents the contractors' access to the land, thereby incurring extra costs (Kucukali 2016) for socio-political reasons, for instance, unsettled land with the owner (Sudirman and Hardjomuljadi 2011), environmental issues, and lack of cooperation between government organizations (Kim et al 2017). The availability of materials and equipment in the local market is also a major factor responsible for increasing project cost as a result of a delayed procurement process (Pall et al 2016).…”
Section: Discussion Of Important Risksmentioning
confidence: 99%
“…The lowest bid price tends to be awfully off-track the realistic project cost (Ahiaga-Dagbui and Smith 2014). It is not uncommon that the lowest bidder in power plant and similar infrastructure projects recoup huge extra amount through change orders at project execution phase (Kim et al 2017;Li and Wang 2016;Liu et al 2017). This study found that ownerinitiated change orders equally contributed to cost overruns and were mainly resulted from poor feasibility study of the project, consultant's lack of knowledge and experience, and owner's additional requirements or changes in design specifications, findings similar to the study by Han and Diekmann (2004).…”
Section: Discussion Of Important Risksmentioning
confidence: 99%
“…This result indicates the emphasis of data acquisition and handover requirements for this complex and complicated 'auxiliary' system. The authors are currently performing the issues of standardized information exchange of equipment and installation in this aspect as well as associated functionality of the NPP schedule [22] and risk [10] management.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…One of the good examples of practical applications is the 'physical breakdown structure (PBS)'. PBS can be defined a hierarchically organized set of physical components that supports automated classifying and integrating mechanisms for managerial purposes [8][9][10]. More often than not, the PBS also encompasses high-level functions and administration components in order to incorporate all aspects of project deliverables [9].…”
Section: Elements For CM Assessment: Structure System Component (Ssc)mentioning
confidence: 99%
“…One of the tools for reducing injuries is the directorate and employees involvement in occupational safety management [15][16][17]. An effective management tool is the analysis and accounting of the negative production risks impact on employees [18].…”
Section: Introductionmentioning
confidence: 99%